IDENTIFIKASI KARAKTERISTIK ALTERASI HIDROTERMAL DAN MINERALISASI ENDAPAN EMAS EPITERMAL DAERAH PROSPEK RAMADA, KECAMATAN CIMANGGU, KABUPATEN PANDEGLANG, PROVINSI BANTEN - Chrishartantyo, Gregorius Agung; Aribowo, Yoga; Widiarso, Dian Agus; Kurniawan, Andi (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Cibaliung Gold Project area is one of the largest primary gold deposits mineralization prospect areas in the western part of Java island which is controlled by PT. Antam (Persero) Tbk.. The research area is part of the Cibaliung Gold Project area called Ramada Prospect. Administratively, Ramada Prospect located in Cimanggu Subdistrict, Pandeglang District, Banten Province. Research conducted aimed to determine the geological condition, characteristics of hydrothermal alteration and gold deposition mineralization, as well as predicting the environmental conditions of hydrothermal constituent.Research conducted with descriptive and qualitative analysis approach. The research method used consists of literature study, field observation, and laboratory test. In the literature study methods conducted assessment of the theoretical basis and previous research. Field survey methods consists of geological mapping, mapping of alteration and mineralization, as well as description and identification of rock core drilling results. In the laboratory test method conducted descriptions and identifications of petrographic, mineragraphy, and X-Ray Diffraction (XRD) to some rock samples and veins, as well as analysis of geological structure stereographic method. The research was also supported by secondary data such as AAS (Atomic Absorption Spectrometry) test results.Lithology of research area consists of tuff rock units, pyroclastic breccia rock units, and andesite lava flow rock units. Pyroclastic breccias rock units and andesite lava flow rock units are interpreted as pre-mineralization rocks, whereas tuff rock units are interpreted as post-mineralization rocks. Based on the analysis of geological structure there is interpreted strike-slip fault has affected geological conditions of the research area. Hydrothermal alteration in the research area can be divided into alteration facies of kaolinite-smectite-chlorite±quartz±carbonate-pyrite replacement-infill strong intensity and alteration facies of chlorite±epidote±sericite±quartz±carbonate-pyrite replacement-infill moderate-strong intensity. Gold deposition mineralization (Au) in the research area predominantly formed on quartz±carbonate veins. The presence of gold associated with silver (Ag) and pyrite (FeS2). The main prospect gold deposits mineralization in the research area contained in